2020
DOI: 10.7759/cureus.8829
|View full text |Cite
|
Sign up to set email alerts
|

Protected Percutaneous Coronary Intervention (PCI) of Cabrol Type Anastomosis of Saphenous Vein Graft (SVG) to the Left Main Coronary Artery (LMCA)

Abstract: The use of percutaneous left ventricular assist devices (VAD) may minimize the risk of hemodynamic compromise during such high-risk percutaneous coronary intervention (PCI) and allow complete revascularization, thus improving outcomes. A good understanding of cardiac hemodynamics is essential in making informed decisions during such cases. A 61-year-old male with an extensive surgical cardiac history including a modified Cabrol type anastomosis with saphenous vein (SVG) conduits to two coronary arteries presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…1,3,6 A patient with a complex surgical cardiac history who had undergone CABG using a modified Cabrol type anastomosis with SVG conduits to two coronary arteries suffered recurrent acute coronary syndrome (ACS), as reported by Sabah et al After coronary angiography revealed significant stenosis in the Cabrol-type SVG grafts, they opted for a protected PCI with Impella support. 8 Since LMCA lesions frequently exhibit aorto-ostial involvement and large, calcified, eccentric plaques, the efficacy of routine PTCA is often compromised. This has led to the widespread routine use of cutting-edge interventional devices like stents, atherectomy, and lasers.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,6 A patient with a complex surgical cardiac history who had undergone CABG using a modified Cabrol type anastomosis with SVG conduits to two coronary arteries suffered recurrent acute coronary syndrome (ACS), as reported by Sabah et al After coronary angiography revealed significant stenosis in the Cabrol-type SVG grafts, they opted for a protected PCI with Impella support. 8 Since LMCA lesions frequently exhibit aorto-ostial involvement and large, calcified, eccentric plaques, the efficacy of routine PTCA is often compromised. This has led to the widespread routine use of cutting-edge interventional devices like stents, atherectomy, and lasers.…”
Section: Discussionmentioning
confidence: 99%
“…In a PubMed search, we found 11 successful PCI cases of anastomotic stenosis or occlusion between the aortocoronary conduit and the LMCA (3)(4)(5)(11)(12)(13)(14)(15)(16)(17)(18). These results are summarized in Supplementary Table 1.…”
Section: Discussionmentioning
confidence: 99%